Harmonization of Regional Regulations in Protecting Island Tourism in Indramayu Regency from the Perspective of State Administrative Law - Sanusi Sanusi; Abd Aziz Tambunan; Dwi Afrimetty Timoera; Muqtadir Ghani Putranto (CV. AFDIFAL MAJU BERKAH, 2026)
This research aims to analyze the harmonization of regional regulations in the development and protection of island tourism in Indramayu Regency from the perspective of State Administrative Law. The focus of the research includes the identification of regional regulatory forms, the regulation of regional government authority, and the mechanism of regulatory harmonization to support the sustainable management of tourist islands. The research method uses a qualitative approach with juridical-normative and descriptive-analytical methods thru the study of regional regulation documents, interviews with Indramayu Regency Dispara officials, and regulatory synchronization analysis. The research results show that regional regulations, including Regional Regulation No. 1/2018, Regional Regulation No. 6/2024, and Regional Regulation on Spatial Planning (RTRW) No. 1/2012, provide a clear normative framework for tourism management, but the effectiveness of implementation is influenced by administrative capacity and fiscal resources. Regulatory harmonization is carried out by aligning the RIPPARKAB with provincial and national regulations, in accordance with the principles of legal harmonization and the general principles of good governance (AUPB), thereby enabling sustainable and accountable island tourism management. This research provides theoretical and practical contributions to strengthening regional tourism governance, bridging the gap between legal norms and policy implementation, and emphasizing the importance of local government administrative capacity.